Analisis Kejadian Stunting terhadap Perkembangan pada Anak Usia 3-5 Tahun di Kecamatan Padalarang Bandung Barat 2023 - Magfira Putri Darna; Lisa Adhia Garina; Dicky Santosa (Bandung Conference Series: Medical Science, 2024)
Abstract. Indonesia is the 4th country in the world and 2nd in Southeast Asia with the highest Stunting rate, namely; 149.2 million cases in 2020. Development in the first 1,000 days is an aspect that is closely related to Stunting, an aspect that can be disrupted in the form of developmental obstacles. This study aims to analyze the relationship between Stunting and development in children aged 3-5 years in Padalarang District, West Bandung. This research is an analytical observational study with a cross sectional approach. Purposive sampling was carried out in the population, the research sample came from primary data taken from filling out questionnaires and measuring body height using a microtoise and entered into the Kuisioner Pra Screening Perkembangan (KKSP). Data were analyzed using univariate and bivariate tests using the Man Whitney test. The number of respondents was 87 children with the characteristics of the respondents being mostly female (51%), with an average age of 45.19 months and most of them were stunted (51), 49% were stunted and 51% were very stunted. The results of the analysis obtained a p value of 0.72 (>0.05) which shows that there is no significant difference between Stunting and development in children aged 3-5 years. Development is influenced by many factors other than nutrition, such as internal factors (mother's role, psychological function) and external factors such as the child's growing environment. Abstrak. Indonesia merupakan negara ke-4 di dunia dan ke-2 di Asia Tenggara dengan angka Stunting tertinggi yaitu; 149,2 juta kasus pada tahun 2020. Perkembangan pada periode 1.000 hari pertama merupakan aspek yang sangat berhubungan erat dengan Stunting, aspek yang dapat terganggu dapat berupa hambatan perkembangan. Penelitian ini bertujuan menganalisis hubungan antara Stunting dan perkembangan pada anak usia 3—5 tahun di Kecamatan Padalarang Bandung Barat. Penelitian ini merupakan penelitian observasional analitik dengan pendekatan cross sectional. Dilakukan purposive sampling pda polulasi, sampel penelitian berasal dari data primer yang diambil dari dari pengisian kuesioner dan pengukuran tinggi badan menggunakan microtoise dan dimasukan ke dalam Kuesioner Pra Skrining Perkembangan (KKSP). Data dianalisis dengan uji univariat dan bivariat dengan uji Man Whitney. Jumlah responden sebanyak 87 anak dengan karakteristik responden mayoritas berjenis kelamin perempuan (51%), dengan rata-rata usia 45,19 bulan dan mayoritas mengalami Stunting (51), pada stunted sebesar 49% dan pada severy stunted sebesar 51% Hasil analisis didapatkan nilai p sebesar 0,72 (>0,05) yang menunjukan bahwa tidak ada perbedaan yang signifikan antara Stunting dan perkembangan pada anak usia 3—5 tahun. Perkembangan dipengaruhi banyak faktor lainnya selain gizi seperti faktor internal (peran ibu, fungsi psikis) dan eksternal seperti lingkungan tumbuh anak.